Small-sided games in young soccer players: physical and technical variables - Italo, S.; Cofano, G. (MOJ Sports Medicine, 2017)
Aim: The Small-sided gamesare very widespread football training exercises to improve both the physical condition and the technical abilities. The aim of the study is to evaluate and compare the internal load of the young football player using the heart rate (HR) and the perceived exertion (RPE) and to describe the type and amount of some technical skills in 3vs3, 4vs4 and 5vs5.